Pengaruh Product, Price, Promotion, dan Place Terhadap Loyalitas Konsumen - Sustiyatik, Enni; Setiono, Beni Agus (Universitas Hang Tuah, 2019)
The purpose of this study was to test and analyze the effect simultaneously and partially Product, Price, Promotion, and Place on customer loyalty. This type of research is an associative study that explains the relationship and influence between Product, Price, Promotion and Place variables on consumer loyalty. The population in this study were consumers who had bought an unknown number of